Cover Feature: An Electrochemically Synthesized Nanoporous Copper Microsensor for Highly Sensitive and Selective Determination of Glyphosate (ChemElectroChem 7/2020). Issue 7 (1st April 2020) - Regiart, Matias; Kumar, Abhishek; Gonçalves, Josué M.; Silva Junior, Gilberto J.; Masini, Jorge César; Angnes, Lúcio; Bertotti, Mauro
Abstract : The Cover Feature shows the generation of a high surface area nanoporous copper structure and its use as a novel platform for indirect electrochemical detection of glyphosate in water samples.More information can be found in the Article by M. Regiart et al .